Response of Yucca gloriosa “Variegata” to Tissue Culture - Abdul-Halem, Ansam G; Alwash, Bushra; Ibrahim, Kadhim M (Al-Nahrain Journal of Science, 2018)
To explore the potential for in vitro rapid regeneration of Spanish dagger (Yucca gloriosa ’Variegata’), different concentrations of 6-Benzyladenine (BA), 1-naphthaleneacetic acid (NAA) and combinations of both were evaluated for callus induction initiated on leaf and bud (terminal and axillary buds) explants using Murashige and Skoog (MS) medium. Callus response induction percentage, fresh weight, color and texture of the callus were assessed after 1.5 and 6.0 months in culture. The appropriate medium for callus initiation on leaf explants was MS medium supplemented with 6.0 mg/L NAA. A combination of 0.2 mg/L BA and 1.5 mg/L NAA also exhibited a remarkable callus induction on bud explants. Effect of thidiazuron (TDZ) addition to the culture medium supplemented with BA and NAA at various concentrations (0.0, 0.1, 0.5 or 1.0 mg/L) was investigated. Faster callus growth and more callus proliferationon from bud explants were observed in MS medium supplemented with 0.1 mg/L BA + 1.5 mg/L NAA + 1 mg/L TDZ. Results showed that TDZ was more effective on callus induction than BA or NAA, however some combinations gave direct shoot regeneration. Calli derived from bud explants were whitish to creamy and compact, while calli derived from leaf explants were greenish.